A novel method for source-specific hemoglobin adducts of nitro-polycyclic aromatic hydrocarbons - Wheelock, K.; J.J. Zhang; McConnell, R.; Tang, D.; Volk, H. E.; Y. Wang; Herbstman, J. B.; S. Wang; Phillips, D. H.; Camann, D.; Gong, J.; Perera, F. (Environ Sci Process Impacts, 2018)
Polycyclic aromatic hydrocarbons (PAH) are ubiquitous air pollutants associated with negative impacts on growth, development and behavior in children. Source-specific biological markers of PAH exposure are needed for targeting interventions to protect children. Nitro-derivatives of PAH can act as markers of exposure to diesel exhaust, gasoline exhaust, or general combustion sources. Using a novel HPLC-APCI-MS/MS detection method, we examined four hemoglobin (Hb) adducts of nitro-PAH metabolites and the Hb adduct of a benzo[a]pyrene (BaP) metabolite in 22 umbilical cord blood samples. The samples were collected from a birth cohort with comprehensive data on prenatal PAH exposure, including prenatal personal air monitoring and DNA adducts in maternal and umbilical cord blood. Using non-parametric analyses, heat maps, and principal component analysis (PCA), we analyzed the relationship between the five Hb adducts and previous PAH measurements, with each measurement representing a different duration of exposure. We found that Hb adducts derived from several diesel-related nitro-PAHs (2-nitrofluorene and 1-nitropyrene) were significantly correlated (r = 0.77, p </= 0.0001) and grouped together in PCA. Nitro-PAH derived Hb adducts were largely unrelated to previously collected measures of exposure to a number of PAH parent compounds. These measures need to be validated in a larger sample.
Keywords: air; atmospheric reactions; benzo(a)pyrene; DNA-adducts; emissions; exhaust; exposure; fluorometric assay; PAH; particulate matter